Cultural determinants of corporate image on an example of Apple Inc. - Woźniak, Jan Fabian (Creativity in Business Practice. Part 2, 2019)
The purpose of the chapter was to analyze the innovative image of Apple Inc. and to show how its creation was influenced by the identity of the organization, corporate culture and leadership of Steve Jobs. The study also describes the differences and similarities between the American national culture and the organizational culture of Apple Inc.